MATERNAL ROLE OF FAMILY RELATIONSHIPS WITH CREATIVITY IN PRE SCHOOL AGE CHILDREN IN SINAR MULYA KINDERGARTEN AT BANDA ACEH CITY IN 2010 - Fahmi Ichwansyah; Dewi Ariani (Pusbindiklat - LIPI, 2011)
Creativity is innate, whose truth value could only be realized if it is nurtured since early age. The important factors to enhance children’s creativity are attention and time. Many mothers have not understood their needed roles to increase children’s creativity. Therefore, further research is needed to know the role of mother as educator, caregiver, protector and its relation to the creativity of preschool age children. This research was done on Sinar Mulia kindergarten at Banda Aceh. Research design was using cross sectional study with a total sample of 50 mothers of Sinar Mulia kindergarten students. Data collection was done using a questionnaire. Then Chi-squaretest was used with α (0.05). Analysis result shows mother’s role in relation to children’s creativity as follows: mother’s role as educators with p-value = 0.005 <0.05, mother’s role as caregiver with p-value = 0.005 <0.05, mother’s role as protector with p-value = 0.001 <0.05. Combined analysis result of mother’s role, shows p-value = 0.020 <0.05. In conclusion there is a relationship between mother’s role as educator, caregiver and protector with pre-school age children creativity at Sinar Mulia kindergarten at Banda Aceh city.